The use of the roter interaction analysis system in assessing veterinary student clinical communication skills during equine wellness examinations in rural Kentucky, USA: A pilot study. Issue 1 (24th November 2021) - Pereira, Mary Mauldin; Artemiou, Elpida; De Pedro, Pedro; Adams, Cindy; Ritter, Caroline
Abstract: Background: Effective clinical communication can aid veterinarians in building good client relationships, increase adherence to recommendations and, ultimately, improve patient health and welfare. However, available information on veterinary communication in the equine context is limited. The objective of this study was to describe the communication of veterinary students in the equine environment who had previous communication training. Additionally, we assessed the suitability of the Roter Interaction Analysis System (RIAS) for the analysis of audio‐video recordings of equine wellness consultations. Methods: Twenty‐seven equine wellness consultations performed by second‐year Ross University School of Veterinary Medicine students were recorded in rural Kentucky, United States of America. Recordings were submitted to a professional coder who applied the RIAS to the equine context by expanding or adjusting code definitions. Results: A substantial amount of utterances (i.e. segments of speech) were allocated to core communication skills including building rapport (30%), facilitation and client activation (24%) and education and counselling (23%). There was a large variation in utterances used among consultations of the same veterinary student and students; they did not appear anxious or nervous. Conclusions: Students made use of core communication skills, indicating that experiences from pre‐clinical training could be transferred to equine practice. Furthermore, this study demonstrated that the RIAS could be considered for consecutive studies aiming to provide observational data on clinical communication in the equine context.